Awareness Regarding Eye Donation among Doctors, Students, and Paramedics at a Tertiary Care Teaching Hospital - Saquib, Mohammed; Mehta, Bhavya; Bhargava, Rahul; Malik, Anu (Nepalese Journal of Ophthalmology, 2023)
Introduction: In the sub-continent, there is a huge discrepancy between the cornea collected and the ever-increasing demand. Lack of awareness, faulty perceptions, and unwillingness to donate corneas are the major hurdles. Objectives: To assess the level of awareness among doctors, students, and paramedics in a teaching hospital.Materials and methods: An analytical cross-sectional, pre-tested, study design assessed the awareness, knowledge, and attitude among health care workers (medical students, nurses, doctors, and paramedics) in the context of eye donation through a administered self-administered semi-structured questionnaire. Results: In our study, 692 (57.7%) of the respondents were aware that the ideal time for donation was within six hours of death. Our study revealed that 875 (72.9) of the respondents were willing to donate their eyes; out of these 305 (25.4%) were MBBS students and 223 (18.6%) were nursing students, (Chi-square tests, p